Efektivitas Bimbingan Konseling Terhadap Peningkatan Kemampuan Penyesuaian Diri AUD di Tk Sekecamatan Bungkal Ponorogo - Ghoziyah, Istifadatul (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2022)
Abstrak: The ability to adapt is an important part that must be possessed by every early childhood in their social environment so that children can socialize in their environment well and be accepted in their new environment. There are several factors that influence the adjustment of early childhood including counseling and also the school environment. The purpose of this study was 1) to determine the effectiveness of counseling guidance on increasing the ability of early childhood adjustment in kindergartens in Bungkal Ponorogo sub-district. This type of research is a quantitative research with comparative causality. The research population is kindergarten in Bungkal Ponorogo District. Data collection with checklists and documentation. The sampling technique used is simple random sampling. To test the validity using product moment correlation and reliability test using Alpha Cronbach. The data analysis technique used was the t-test analysis formula. The results showed that the mean values in the two schools were different and higher in kindergartens with counseling guidance services than in kindergartens without counseling services. Counseling Guidance services provided by Counseling Guidance teachers to direct the child's adjustment well in a more personal manner. Such as providing liaison books for parents, providing intensive guidance to children whose initial adjustment is still low so that they become well suited to their development.Keywords: counseling guidance service, self-adjustment ability